No-Man’s Land:: Mythic Crisis in Gwendolyn MacEwen’s The T.E. Lawrence Poems - Wood, Brent (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2004)
In general, the contemporary thrust of poetry in terms of myth is not toward orthodoxy of belief and action but toward a plurality and constant evolution. Literary poetry today is an embodiment of a certain kind of myth-telling that is much more concerned with the introduction of new ideas, with cross-cultural mythological imagination, and with making a space for meditation. In The T.E. Lawrence Poems, Gwendolyn MacEwen seeks to illuminate the reader's own personal relationship with myth, and, through an investigation of T.E. Lawrence's pattern of identification with the Other, to explore how the poetic imagination copes with bringing cultural and personal myths to the surface.